Genetic background of behavior traits in lactating sows under heat-stress conditions and their relationship with heat tolerance and maternal performance traits - Hartman, Sharlene O.; Benfica, Lorena F.; Johnson, Jay S.; Marchant, Jeremy N.; Oliveira, Hinayah R.; Pedrosa, Victor B.; Schinckel, Allan P.; Huang, Yijian; Gloria, Leonardo S.; Wen, Hui; Brito, Luiz F. (Frontiers in Genetics, 2025)
Heat stress is among the most significant welfare challenges facing modern swine production systems worldwide. Pigs are particularly susceptible to heat stress due to their inactive sudoriferous glands, which limits their capacity for evaporative cooling. As a result, they rely predominantly on behavioral strategies for thermoregulation. This behavioral dependence underscores the potential value of integrating behavioral assessments with genetic analyses to identify heritable components of climatic resilience. In this context, the main objectives of this study were as follows: 1) to develop an ethogram to evaluate the response of lactating sows to a novel event (i.e., hair shaving); 2) to derive the traits’ responsiveness score (RS), vocalization score (VS), and shave time (ST) from the ethogram, and identify key systematic effects influencing these behavioral responses of lactating sows under heat-stress conditions; 3) to estimate variance components for all the derived traits; 4) to assess genetic correlations between the behavioral traits and both direct indicators of heat tolerance and maternal ability traits; and 5) to perform genome-wide association studies (GWAS) to identify genomic regions associated with sow behavioral traits. RS, VS, and ST were found to be heritable with heritability estimates of 0.17 ± 0.05, 0.15 ± 0.05, and 0.10 ± 0.05, respectively. These traits had null-to-low genetic correlations with maternal performance and low-to-moderate genetic correlations with direct indicators of heat tolerance. Twelve genomic markers were found to be significantly associated with the three behavioral traits, including regions overlapping with genes known to influence heat stress response, such as PIK3R5 and NCF2. In conclusion, sow behavioral responses to a novel event under heat-stress conditions are heritable and highly polygenic but uncorrelated or lowly correlated with climatic resilience and maternal traits.